Video vs. direct laryngoscopy for tracheal intubation in neonates: a meta-analysis - Li, Xiang; Zhang, Xulin; Chen, Dongxu; Yu, Chao; Jiang, Xiaoqin (Frontiers in Pediatrics, 2025)
PurposeThis study aimed to synthesize data from randomized controlled trials (RCTs) evaluating the effectiveness and safety of videolaryngoscopy vs. direct laryngoscopy in neonates undergoing endotracheal intubation.MethodsThis meta-analysis was conducted on June 1, 2024, in MEDLINE, Embase, Cochrane Central, and CINAHL EbscoHost databases to identify relevant trials. Primary outcome was the success rate of intubation on the first attempt. Secondary outcomes included the time required for successful intubation, number of intubation attempts, adverse events related to both non-airway and airway complications. Trial sequential analysis (TSA) was performed to rule out the possibility of false positive result.ResultsNine RCTs involving 1,059 neonates were included. Videolaryngoscopy significantly improved the success rate of first-attempt intubation [risk ratio (RR) 1.21, 95% CI 1.06–1.38], TSA conﬁrmed these findings. Subgroup analyses indicated that videolaryngoscopy was particularly beneficial for inexperienced clinicians or when used in the neonatal intensive care unit. However, videolaryngoscopy did not significantly reduce the number of intubation attempts [mean difference (MD) −0.22, 95% CI −0.44–0.01] and had a similar time to successful intubation as direct laryngoscopy (MD 0.91, 95% CI −0.32–2.14). Videolaryngoscopy was associated with less airway trauma (RR 0.23, 95% CI 0.06–0.89). Additionally, videolaryngoscopy showed minimal differences in the occurrence of bradycardia, desaturation, or low oxygen saturation levels during intubation.ConclusionThe current evidence suggested that videolaryngoscopy enhanced the success rate of first-attempt intubation and reduced airway trauma, while requiring a similar time required for successful intubation compared to direct laryngoscopy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024552392, PROSPERO CRD42024552392.